2020
DOI: 10.1002/acs.3144
|View full text |Cite
|
Sign up to set email alerts
|

An integrated fault estimation and fault tolerant control method using H‐based adaptive observers

Abstract: Summary An integrated fault estimation/fault‐tolerant control (FTC) scheme is developed in this article for nonlinear Lipschitz systems in the presence of external disturbances and actuator failures. To address this problem, coupled uncertainties between the observer error dynamics and the control system are considered, which is conveniently ignored in control approaches based on the separation principle. An H∞‐based adaptive observer is proposed to simultaneously estimate the system states and actuator faults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 37 publications
(87 reference statements)
0
17
0
Order By: Relevance
“…Remark Compared with the existing adaptive observers, 25,32 the restriction mentioned in () is convenient. According to Assumption 1, in the work of Raoufi et al, 36 it is indicated that the equality PE=CTR$$ PE={C}^TR $$ is satisfied if and only if rankfalse(CEfalse)=rankfalse(Efalse)$$ \mathit{\operatorname{rank}}(CE)=\mathit{\operatorname{rank}}(E) $$.…”
Section: D‐oeeo Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark Compared with the existing adaptive observers, 25,32 the restriction mentioned in () is convenient. According to Assumption 1, in the work of Raoufi et al, 36 it is indicated that the equality PE=CTR$$ PE={C}^TR $$ is satisfied if and only if rankfalse(CEfalse)=rankfalse(Efalse)$$ \mathit{\operatorname{rank}}(CE)=\mathit{\operatorname{rank}}(E) $$.…”
Section: D‐oeeo Designmentioning
confidence: 99%
“…The fixed‐time tracking consensus problem of high‐order nonlinear MASs with actuator faults and performance constraint is investigated in the work of Yang et al 23 A new distributed fault‐tolerant control scheme based on the static output feedback for interconnected systems is developed by Zhang et al Based on the associated information, a distributed fault estimator can improve the accuracy of fault estimation information 24 . In the work of Fazeli and Abedi, 25 an integrated fault estimation and fault‐tolerant control scheme is proposed for the nonlinear Lipschitz systems with external disturbances and actuator faults. The designed observer‐based distributed fault‐tolerant consensus tracking control (D‐FTCTC) scheme with a distributed fashion can ensure an effective compensation and tolerance for actuator faults of Lipschitz nonlinear MASs, while achieving the state consensus tracking target.…”
Section: Introductionmentioning
confidence: 99%
“…In [24], actuator faults, external disturbances, and uncertain inertia parameter of a rigid spacecraft are regard as a lumped disturbance together, which is estimated via a finite‐time disturbance observer. Considering the coupling effect between the observer error dynamics and the control system, an H${H_\infty }$ based adaptive observer is developed for nonlinear Lipschitz systems in the presence of external disturbances and actuator faults [25]. More results on the fault diagnosis including the quantitative and qualitative methods for continuous‐time systems and discrete‐time systems can be found in [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it is of great significance to study the fault-tolerant control under the actuator fault. [15][16][17][18][19] On the other hand, the prior information of the control coefficient is required in most literature, while it is difficult to detect in some cases. [20][21][22] Therefore, it is more reasonable to study the case that the control coefficient is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Deviations in the characteristics of the control input signal can cause the actuator fault, which reduces the safety and reliability of system. Hence, it is of great significance to study the fault‐tolerant control under the actuator fault 15‐19 . On the other hand, the prior information of the control coefficient is required in most literature, while it is difficult to detect in some cases 20‐22 .…”
Section: Introductionmentioning
confidence: 99%